15+2×{[3×(5^17÷5^15)-2^3×9÷3^2+3×(10+1^2017)]÷2^2}
Răspunsuri la întrebare
Răspuns de
1
15+2×{[3×(5^17÷5^15)-2^3×9÷3^2+3×(10+1^2017)]÷2^2}=15+2×{[3×(5^2)-2^3×9÷3^2+3×(10+1)]÷2^2}=
15+2×[(3×25-2^3×3^0+3×11)÷2^2]=15+2×[(75-2^3×1+33)÷2^2]=15+2×[(75-8+33)÷2^2]=15+2×(100÷4)=15+2×25=15+50=65
15+2×[(3×25-2^3×3^0+3×11)÷2^2]=15+2×[(75-2^3×1+33)÷2^2]=15+2×[(75-8+33)÷2^2]=15+2×(100÷4)=15+2×25=15+50=65
Alte întrebări interesante
Chimie,
8 ani în urmă
Istorie,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă